MELEJITKAN PRESTASI BELAJAR BAHASA INGGRIS MELALUI PEMBELAJARAN KOOPERATIF MODEL NUMBERED HEAD TOGETHER PADA SISWA SMP NEGERI 1 DAMPAL SELATAN - Fatimah Fatimah (Scolae: Journal of Pedagogy, 2019)
The various negative impacts of using these group work methods should be avoided if only the teacher is willing to spend more time and attention in preparing and constructing group work methods. What is introduced in cooperative learning methods is not just group work, but the structuring. Thus, cooperative learning teaching systems can be defined as structured group work / learning. Included in this structure are five main elements (Johnson & Johnson, 1993), namely positive interdependence, individual responsibility, personal interaction, collaboration skills, and group processes. The objectives of this study are: (a) To reveal the effect of Numbered Head Together cooperative learning on English learning outcomes. (b) to find out how far the understanding and mastery of English subjects after the application of cooperative learning Numbered Head Together model. This research uses action research as much as three rounds. Each round consists of four stages: design, activity and observation, reflection, and refinement. The targets of this study were students of South Dampal 1 Middle School. The data obtained in the form of formative test results, observation sheets of teaching and learning activities. From the results of the analyst found that student achievement has increased from cycle I to cycle III namely, cycle I (60.71%), cycle II (75.00%), cycle III (89.29%). The conclusion of this research is the cooperative method of the Numbered Head Together model can positively influence student motivation.